School Based Tooth Brushing and Annual Silver Diammine Fluoride Application as a Highest Priority Package for Achieving Universal Oral Health Care for Cambodian Children - Turton, Bathsheba; Patel, Jilen; Sieng, Chanthyda; Tak, Ranuch; Durward, Callum (Frontiers in Oral Health, 2021)
Background: Achieving Universal Oral Health Care among Low-to Middle-Income settings is challenging and little literature exists around exploring what a ‘Highest Priority Package’ of care might look like in the context of oral health. The Healthy Kids Cambodia (HKC) program differs from most conventional school dental services in that the initial package of care that is offered is daily toothbrushing with 1500ppm fluoride toothpaste (DTB) together with the topical application of Silver Diamine fluoride (SDF) for management of lesions in primary teeth. Aim: To examine tooth level outcomes for 8-to 10-year old children from two schools that performed DTB with application of SDF at differing time-points. Design: This was an observational cohort study that examined lesion progression among children in late mixed dentition at two schools. Data were collected using the dmft and pufa indices. Both schools received materials and training for DTB at baseline. School One received SDF at baseline while School Two received SDF after 9-months. Intraoral examinations were performed and the presentation of primary teeth with cavitated carious lesions were compared at baseline and 12m. If a tooth was still caries-active or had become pulpally involved, this was considered to be an unacceptable outcome. Descriptive analysis was performed the chi-squared test was used to examine differences in the proportion of teeth with unacceptable outcomes by school membership. Results: Of the 521 children recruited, 470 (90.2%) were followed. Where there was a delay in SDF application (School 2) there was a three times greater chance of an unacceptable outcome. 10% of primary teeth in School One and 33% of primary teeth in the School Two had unacceptable outcomes. Conclusion: The present study offers data on expected effect sizes that might inform future step-wedged clinical trials to validate an oral health Highest Priority Package of care for Cambodian children. The delivery of a package of care that includes both DTB and SDF can prevent adverse outcomes, such as dental infections, in primary teeth with carious lesions.